Damping Harmonic Distortion Using Active Filter with PID Control at Udayana University Faculty of Engineering Bukit Jimbaran - Suartika, I Made; Hartati, Rukmi Sari; Manuaba, I.B.G. (Journal of Electrical, Electronics and Informatics; Vol 2 No 2 (2018): JEEI (August 2018), 2018)
Increased THD (Total Harmonics Distortion) in the utility, caused by the increasing operation of non-linear loads. High THD current (THDi) will affect the increase of power losses in the power system. In this study, THD analysis of the simulation results was performed according to IEEE 519-2014 standard on existing condition, shunt active filter operating condition and shunt active filter operating conditions with PID (proportional integral derivative) control, also analyzed losses before and after harmonic impact. The result of losses analysis on existing condition: losses phases R 3.38%, phase S 2.29%, phase T 3.33%. Total losses on existing condition 9.01%. Operation with active shunt filter is obtained losses for phase R 1.60%, phase S 2.46%, phase T 1.67%, so the total losses become 5.73%. While using the active filter with PID control for losses phase R 1.02%, phases S 0.89%, phases T 0.99%, so the total losses fell to 2.18%